Cyber-Security and Critical Infrastructure Protection: The Case of Iceland - Jón Kristinn Ragnarsson 1981- (2010)
Most modern countries depend on computers to a certain degree. With higher dependence the risk involved increases, as a single system failure could make a serious dent in a state's infrastructure. Cyber-threats have become one of the best-known threats of the modern world, and can be divided into several categories ranging from those affecting the security of the individual to serious matters of state. They come in turn from state, private-sector and individual sources and have already led to several crises of international significance. Iceland has long been proud to be in the forefront of many technological advances, and for instance the usage of computers in Iceland is among the highest in the world. But in the case of technological advances, security advances must follow or the whole state becomes vulnerable. In the modern world there are several options for a state that wants to improve its cyber-security, including chances to cooperate with various international agencies. In this thesis Iceland is examined in terms of cyber-vulnerabilities relating especially to critical infrastructure. It will be asked what efforts Iceland has already made in this field but more importantly what efforts still need to be undertaken, drawing upon the opinions of several experts at different levels in both government and the private sector. Iceland has long been rather passive when it comes to international cooperation in security, and many reasons for this can be found including most recently the crisis now gripping the country. It can however be assumed that this crisis will one day pass over. The question is whether it will then be too late to start to look at security measures for the country. As will be revealed in this thesis, not all international measures need to require much funding, and international cooperation can be beneficial for all concerned.